The role of allometry and posture in the evolution of the hominin subaxial cervical spine. Issue 104 (March 2017) - Arlegi, Mikel; Gómez-Olivencia, Asier; Albessard, Lou; Martínez, Ignacio; Balzeau, Antoine; Arsuaga, Juan Luis; Been, Ella
Abstract: Cervical vertebrae not only protect the spinal cord but also are the insertion and origin points for muscles related to the movement of the head, upper limb, and trunk, among others, and are thus important elements in primate evolution. While previous work has been undertaken on the first two cervical vertebrae, there is a dearth of studies on the subaxial cervical spine in hominines. In this paper, we provide detailed morphological information on two important aspects of the subaxial cervical vertebrae (C3 – C7): mid-sagittal morphology and superior facet orientation. We studied large samples of African apes including modern humans and the most complete fossil hominin subaxial cervical vertebrae using both traditional and geometric morphometrics. There are significant differences between extant hominoids related to the relative length and orientation of the spinous process as well as to the orientation of the articular facets, which are related to size, locomotion, and neck posture. In fact, fossil hominins do not completely conform to any of the extant groups. Our assessment of mid-sagittal morphology and superior articular facet orientation shows that australopiths have more Homo -like upper subaxial cervical vertebrae coupled with more "primitive" lower cervical vertebrae. Based on these results, we hypothesize that those changes, maybe related to postural changes derived from bipedalism, did not affect the entire subaxial cervical spine at once. From a methodological point of view, the combination of traditional and geometric morphometric data provides a more integrative perspective of morphological change and evolution, which is certainly useful in human evolutionary studies.